2018
DOI: 10.1111/jcmm.13731
|View full text |Cite
|
Sign up to set email alerts
|

Combination of resveratrol and 5‐azacytydine improves osteogenesis of metabolic syndrome mesenchymal stem cells

Abstract: Endocrine disorders have become more and more frequently diagnosed in humans and animals. In horses, equine metabolic syndrome (EMS) is characterized by insulin resistance, hyperleptinemia, hyperinsulinemia, inflammation and usually by pathological obesity. Due to an increased inflammatory response in the adipose tissue, cytophysiological properties of adipose derived stem cells (ASC) have been impaired, which strongly limits their therapeutic potential. Excessive accumulation of reactive oxygen species, mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
(117 reference statements)
2
20
0
Order By: Relevance
“…The Parkin is a crucial mitophagy regulator and its activation can build ubiquitin chains to ubiquitinating outer membrane protein on damaged mitochondria to label them for degradation in lysosomes (Bingol and Sheng, 2016). These findings are consistent with previous research by the same team, which showed that increased ASC apoptosis derived from EMS horses resulted in enhanced mitochondrial fission compared with the healthy control (Marycz et al, 2018). Similarly, metabolic syndrome impairs the swine ASC mitochondrial structure featured by an increase in mitochondrial fission and reduction of mitochondrial fusion (Farahani et al, 2020).…”
Section: Mitochondrial Dynamics In Mscs Under Metabolic Stresssupporting
confidence: 87%
See 1 more Smart Citation
“…The Parkin is a crucial mitophagy regulator and its activation can build ubiquitin chains to ubiquitinating outer membrane protein on damaged mitochondria to label them for degradation in lysosomes (Bingol and Sheng, 2016). These findings are consistent with previous research by the same team, which showed that increased ASC apoptosis derived from EMS horses resulted in enhanced mitochondrial fission compared with the healthy control (Marycz et al, 2018). Similarly, metabolic syndrome impairs the swine ASC mitochondrial structure featured by an increase in mitochondrial fission and reduction of mitochondrial fusion (Farahani et al, 2020).…”
Section: Mitochondrial Dynamics In Mscs Under Metabolic Stresssupporting
confidence: 87%
“…According to the literature, stress often results in fragmentation but not elongation events in mitochondria in MSCs, which is attributed to dramatic enhanced mitochondrial fission with/without inhibited mitochondrial fusion (He et al, 2018;Marycz et al, 2018;Shen et al, 2018a;Ma et al, 2019). In addition, the suppression effect on both mitochondrial fission and fusion was observed in BMSCs when they were treated with high levels of ferric ammonium citrate, a commonly used agent to induce iron overload (Yao et al, 2019).…”
Section: Multifaceted Effects Of Mitochondrial Dynamics Under Stressmentioning
confidence: 99%
“…Electrophoresis was performed from samples with equal amounts of protein (30 μg). SDS-PAGE and the protein transfer were completed using protocols described previously [34,35]. Primary antibodies against BDNF (SAB2108004, Sigma Aldrich, Poznan, Poland) were prepared at a dilution of 1:250 in Tris/NaCl/Tween buffer (TBST).…”
Section: Methodsmentioning
confidence: 99%
“…All flow cytometry analyses were performed after 24 hours of chondrogenic differentiation as described previously [38]. Cells were incubated with anti-5-mC antibody (Abcam, ab73938) and anti-histone H3 (Abcam, ab8898) with 10% goat serum.…”
Section: Methodsmentioning
confidence: 99%